As we have (x+1) (x+2) we can use substitution to solve and find the third factor. Remember that these factors are true when y or f(x) = 0

x^3+ax^2+bx-10 Substitute the two values you have (x=-1; x= -2)

`f(-1)= (-1)^3 + a(-1)^2 + b(-1) - 10`

`therefore 0= -1 +a - b - 10` multiply this line by 2. You'll see...

(The entire section contains 182 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.